Measurement of the differential cross section for isolated prompt photon production in pp collisions at 7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2011)
A measurement of the differential cross section for the inclusive production of isolated prompt photons in proton-proton collisions at a center-of-mass energy of 7 TeV is presented. The data sample corresponds to an integrated luminosity of 36pb-1 recorded by the CMS detector at the LHC. The measurement covers the pseudorapidity range |η|<2.5 and the transverse energy range 25